2019
DOI: 10.1038/s41388-019-1107-9
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 accelerates the hepatitis B virus X-induced malignant transformation of hepatic progenitor cells by upregulating miR-199a-3p

Abstract: Increasing evidence has suggested that liver cancer arises partially from transformed hepatic progenitor cells (HPCs). However, the detailed mechanisms underlying HPC transformation are poorly understood. In this study, we provide evidence linking the coexistence of hepatitis B virus X protein (HBx) and transforming growth factor beta 1 (TGF-β1) with miR-199a-3p in the malignant transformation of HPCs. The examination of liver cancer specimens demonstrated that HBx and TGF-β1 expression was positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…TGF-β1 cooperation with HBx can activate the c-Jun N-terminal kinase (JNK)/c-Jun pathway, while miR-199a-3p, a regulator of hepatic progenitor cell (HPC) transformation, can be activated by c-Jun. In conclusion, TGF-β1/HBx co-regulated the miR-199a-3p signaling axis targeting malignant transformation of HPCs ( Dong et al, 2019 ). Furthermore, miR-155 overexpression promoted cell EMT in liver cancer cells, and overexpression of miR-155 promoted the stemness of LCSCs via down-regulation of tumor protein P53 inducible nuclear protein 1 (TP53INP1), which is a downstream target gene of miR-155.…”
Section: The Role and Classification Of Ncrnasmentioning
confidence: 95%
“…TGF-β1 cooperation with HBx can activate the c-Jun N-terminal kinase (JNK)/c-Jun pathway, while miR-199a-3p, a regulator of hepatic progenitor cell (HPC) transformation, can be activated by c-Jun. In conclusion, TGF-β1/HBx co-regulated the miR-199a-3p signaling axis targeting malignant transformation of HPCs ( Dong et al, 2019 ). Furthermore, miR-155 overexpression promoted cell EMT in liver cancer cells, and overexpression of miR-155 promoted the stemness of LCSCs via down-regulation of tumor protein P53 inducible nuclear protein 1 (TP53INP1), which is a downstream target gene of miR-155.…”
Section: The Role and Classification Of Ncrnasmentioning
confidence: 95%
“…Although some studies reported the anti-HBV action of TGF-β [ 107 ], it has also been suggested that HBV infection upregulated the expression of TGF-β [ 108 , 109 , 110 , 111 ], which might be related to the inhibition of immune responses, as well as the development of fibrosis and intra hepatic cholangiocarcinoma [ 110 , 111 ]. The mechanisms whereby TGF-β regulates liver pathogenesis during chronic HBV infection includes but is not restricted to the regulation of extracellular matrix system [ 112 ], regulation of immune modulators such as Th17 and regulatory T cells (Tregs) [ 113 , 114 ], production of cytokines and chemokines [ 115 ], regulation of miRNA signaling [ 116 ], and cell proliferation [ 117 ].…”
Section: Liver Regeneration and Hccmentioning
confidence: 99%
“…Of note, CD13 expression positively correlates with metastatic lung foci, suggesting that miR-125b mimics can inhibit the CSC population in HCC [ 83 ]. Interestingly, HBx and TGF-β1 overexpression led to c-Jun N-terminal kinase (JNK)/c-Jun-mediated miR-199a-3p upregulation in the rat-derived hepatic stem cell line LE/6, helping to trigger stem cell-like characteristics in vitro and increased in vivo tumorigenesis [ 84 ]. Despite its well-known role as a tumor suppressor miRNA, this study suggests a possible role for miR-199a-3p in the induction and maintenance of the CSC population in HCC.…”
Section: Csc Targeting and Therapeutic Implicationsmentioning
confidence: 99%